Effects of broussonetia papyrifera-fermented feed on production performance, egg quality, and caecal microbiota of laying hens during the late laying period. Issue 1 (31st December 2022) - Zhu, Yipu; Tao, Zhenyang; Chen, Xiaochen; Xiao, Jianshe; Zhang, Yanda; Wang, Zhanbin
Abstract: This study was conducted to determine the effects of different proportions of Broussonetia papyrifera (BP)-fermented feed in the diet to replace part of soybean meal on the production performance, egg quality and caecal microbiota of laying hens in the late laying period. In the experiment, 360 Hy-line brown laying hens (67-week-old) were randomly divided into 4 groups with 6 replicates in each group and 15 chickens in each replicate. The control group was fed with basic diets, and EG1, EG2 and EG3 groups were used in 1.5%, 3% and 4.5% BP-fermented feed to replace corn and soybean meal in the basic diet, respectively. The pre-feeding period was 7 days, and the experiment period was 56 days. In terms of production performance, the average daily egg production in the EG3 decreased significantly compared with that in the control group ( p < .05). In terms of caecal microorganisms, the abundance indices of Sobs, Chao, and ACE community distribution in EG2 significantly increased compared with those in the control group ( p < .05). At the phylum level, the abundance of WPS-2 in all experimental groups significantly increased ( p < .05). The abundance of Actinobacteria in EG1 increased significantly, and that of Campilobacterota and Elusimicrobiota in EG2 significantly increased ( p < .05). At the genus level, Olsenella in EG1 increased significantly ( p <.05) and UCG-008 in EG3 increased significantly ( p < .05) with increasing replacement ratio of BP-fermented feed compared with the control group. The results suggest that based on the production performance, the recommended replacement amount is 3%. Highlights: BP-fermented feed can be used as a new protein feed in layers diet at late laying stages. BP-fermented feed had no significant impact on improved egg production performance and egg quality. Replacing part of soybean meal with BP-fermented feed can significantly increase the WPS-2 and Actinobacteria and other phyla, resulting in changes in the intestinal microbes of laying hens.